Recent range expansion and lineage idiosyncratic population structure of Liodessus diving beetles in the high Andes (Coleoptera: Dytiscidae, Bidessini). - Michael Balke; Tobias Mainda; Katja Neven; Lars Hendrich; Michael Steven Basantes; Carlos Prieto; Adrián Villastrigo (PLoS ONE)
Here, we review the taxonomy and population genetic structure of diving beetles in the genus Liodessus Guignot, 1939 from the high Andes of southern Colombia and Ecuador. Liodessus quillacinga ecuadoriensis ssp. nov. is described from the type locality Otavalo, Laguna San Pablo. Liodessus quimbaya azufralis Megna, Hendrich & Balke, 2019 stat. nov. is now regarded as a subspecies of Liodessus quimbaya Megna, Hendrich & Balke, 2019 based on new morphological and genetical data. Liodessus quimbaya paletara ssp. nov. is described from the Paletará Valley (Colombia: Cauca).